BAGAN PENGERINGAN BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Efrida Basri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
This paper describes a kiln drying experiment of wood, with several species that proposed as industrial timber estate. There are eight species were investigated five of which taken from natural forest, while the others are from plantation. The experiment was conducted in two stages, quick drying tests in an electrical oven and actual drying in two small dry kilns. Result of quick drying tests are rough kiln schedules and the schedules were tested in the small kilns.Drying properties of wood taken from natural forest are practically similar to those of plantation stands, Tengkawang, begontoi, kuntui, damar mata kucing and jeungjing have the same kiln drying schedule.